Application of Flue Gas Cleaning Technologies for Solid Fuel Boilers of Combine Heat and Power Plants - Serhii V. Horianoi; Ihor A. Volchyn (Journal of Mechanical Engineering)
The ways to achieve the requirements of modern environmental legislation of Ukraine and the European Union regarding the limiting emissions of pollutants from large and medium-sized combustion plants concerning the solid fuel steam boilers of municipal and industrial combine heat and power plants (CHPP) in Ukraine is analyzed in the paper. The environmental requirements and technologies for cleaning flue gases of solid fuel boilers from the main pollutants, namely particulate matter, sulfur dioxide and nitrogen oxides, were considered, and the effectiveness, advantages and limitations for the implementation of these technologies on existing boilers of thermal power plants were analyzed. The existing state of gas cleaning equipment, put into operation more than fifty years ago, does not meet current environmental requirements, and the urgent issue is the reconstruction and modernization of existing and the construction of new gas cleaning plants. The use of fabric filters, electrostatic filters and wet scrubbers with a Venturi tube will allow to fulfill the requirements of European directives on dust emission limit values, and the most rational solution will be to use the existing wet scrubbers with a Venturi tube, which are equipped on the vast majority of CHPPs, by significantly increasing the specific flow rate of liquid for irrigation. For the capture of gaseous pollutants, a promising direction is the use of ammonium reagents for highly efficient desulfurization and obtaining ammonium sulfate as a desulfurization product, which is a mineral fertilizer, and the reduction of nitrogen oxides to molecular nitrogen. The use of an aqueous solution of ammonia in a wet scrubber with a Venturi tube will allow to simultaneously capture fly ash and sulfur dioxide in one device. To reduce nitrogen oxide emissions in CHPP boilers, it is advisable from the point of view of investment costs and spatial conditions to use the method of selective non-catalytic reduction.